THX 1138 - Schifrin, Lalo 1932- (Warner Home Video Germany, 2004)
"A man whose mind and body are controlled by the government ... makes a harrowing attempt to escape from a world where thoughts are controlled, freedom is an impossibility and love is the ultimate crime"--Container.
Original: USA, 1970
Enthält: DVD 1 (Hauptfilm ; Original Kommentar von Co-Autor/ Regisseur George Lucas und Co-Autor/Sounddesigner Walter Murch ; Theater of Noise Tonspur nur mit Sound-Effekten sowie Master Sessions, eine Reihe von Video Segmenten, die Murchs Pionierarbeit vorstellen) ; DVD 2 (2 neue Dokumentationen "Ein Vermächtnis der Filmemacher: die ersten Jahre von American Zeotrope" und "Ein Artefakt aus der Zukunft: Das Making of THX 1138" ; "Ein elektronisches Labyrinth: THX 1138 4EB", der ursprüngliche Studentenfilm von George Lucas ; Produktionsdokumentation von den Dreharbeiten: "Bald")
Bildformat: 2.40:1 (16:9)
Keywords: Androids -- Drama; Brainwashing -- Drama; Film; DVD-Video; Feature films; Future in motion pictures; Science fiction films; Video recordings for the hearing impaired